Research on Vibration Reduction in the Transmission System of Plastic Centrifugal Pump - Lili Zhang; Lingfeng Tang; Qingzhao Wen (Applied Sciences, 2024)
The inherent weakness in the deformation resistance of plastic centrifugal pumps makes them prone to vibrations. This study explores the impact of flow components on the vibrations of such pumps. Utilizing the given parameters, the primary structural parameters of the plastic centrifugal pump were calculated. The study focused on the torsional vibrations within the pump shaft transmission system, employing a silicone oil damper for vibration mitigation. A dual-mass forced torsion vibration model was developed for the pump shaft transmission system with the added damper. The optimal damping coefficient for this damper was determined, and its structural design was completed, including the creation of three-dimensional models and two-dimensional part drawings. Utilizing a ZT-3 type rotor test bench, a mathematical model correlating centrifugal pump speed with deflection was developed, and the effectiveness of various polynomials was assessed. The analysis showed that the optimal damping value for the silicone oil damper is 0.22. Compared to the system without the damper, the vibration frequency reduced by 10.45%, and the vibration amplitude decreased by 49.29%, demonstrating excellent vibration reduction effectiveness.